Investigating the Dependence of Radiative Feedbacks on Patterns of Forcing and Surface Temperature Change - Haugstad, Alexander David (My University, 2017)
Radiative feedbacks robustly vary over time in transient warming simulations. Published studies offer two explanations: (i) evolving patterns of ocean heat uptake (OHU) or radiative forcing give rise to OHU or forcing efficacies, and (ii) evolving patterns of surface temperature change. This study seeks to determine whether these explanations are indeed distinct/different. By first using an idealized framework of an aquaplanet atmosphere-only model, we show radiative feedbacks depend on the pattern of climate forcing. Yet, the same feedbacks arise when the temperature pattern induced by that climate forcing is prescribed in the absence of any forcing. These findings suggest the perspective that feedbacks are influenced by efficacies of forcing and OHU is equivalent to the perspective that feedbacks are dependent on the temperature patterns induced by those forcings. We additionally show that, while there are slight caveats when sea ice and land are included, in general this result holds in more realistic model setups. Thus, prescribed surface temperature simulations are valuable for studying the transient evolution of radiative feedbacks.
Thesis (Master's)--University of Washington, 2017-08
Keywords: Climate; Feedbacks; GCMs; OHU; Radiative; Sensitivity; Atmospheric sciences; Atmospheric sciences